The Hypotension Prediction Index in Free Flap Transplant in Head and Neck Surgery: Protocol of a Prospective Randomized Controlled Trial - Jakub Szrama; Agata Gradys; Amadeusz Woźniak; Zuzanna Nowak; Tomasz Bartkowiak; Ashish Lohani; Krzysztof Zwoliński; Tomasz Koszel; Krzysztof Kusza (Life)
Introduction: Microvascular free flap surgery is a treatment method for patients with head and neck cancer requiring reconstruction surgery. Patients undergoing this complex, long-lasting surgery are prone to prolonged episodes of intraoperative hypotension, which is associated with increased incidence of postoperative mortality, morbidity, and free flap failure. A new technology recently approved, named the Hypotension Prediction Index (HPI), allows precise hemodynamic monitoring of patients under general anesthesia, with a significant reduction of intraoperative hypotension events. This study aims to assess the impact of the Hypotension Prediction Index (HPI) on the incidence and severity of intraoperative hypotension in patients undergoing free flap surgery. Methods and analysis: Eligible patients will be randomly assigned to one of two groups: Group A, receiving invasive blood pressure monitoring with standard medical therapy, or Group B, undergoing hemodynamic monitoring using the Hypotension Prediction Index (HPI) software. The primary outcome is the time-weighted average (TWA) of mean arterial pressure (MAP) < 65 mmHg. Secondary outcomes include free flap viability and perioperative complications. Ethics and dissemination: Ethics approval was obtained from the Poznan University of Medical Sciences Ethics Committee (KB-560/22; date 1 July 2022). Results will be submitted for publication in a peer-reviewed journal. Trial registration number: NCT 05738603.